Cost‐Effectiveness and Public Health Effect of Influenza Vaccine Strategies for U.S. Elderly Adults. Issue 10 (6th October 2016) - Raviotta, Jonathan M.; Smith, Kenneth J.; DePasse, Jay; Brown, Shawn T.; Shim, Eunha; Nowalk, Mary Patricia; Zimmerman, Richard K.
Abstract : Objectives: To compare the cost‐effectiveness of four influenza vaccines available in the United States for persons aged 65 and older: trivalent inactivated influenza vaccine (IIV3), quadrivalent inactivated influenza vaccine (IIV4), a more‐expensive high‐dose IIV3, and a newly approved adjuvanted IIV3. Design: Cost‐effectiveness analysis using a Markov model and sensitivity analyses. Setting: A hypothetical influenza vaccination season modeled according to possible U.S. influenza vaccination policies. Participants: Hypothetical cohort of individuals aged 65 and older in the United States. Measurements: Cost‐effectiveness and public health benefits of available influenza vaccination strategies in U.S. elderly adults. Results: IIV3 cost $3, 690 per quality‐adjusted life year (QALY) gained, IIV4 cost $20, 939 more than IIV3 per QALY gained, and high‐dose IIV3 cost $31, 214 more per QALY than IIV4. The model projected 83, 775 fewer influenza cases and 980 fewer deaths with high‐dose IIV3 than with the next most‐effective vaccine: IIV4. In a probabilistic sensitivity analysis, high‐dose IIV3 was the favored strategy if willingness to pay is $25, 000 or more per QALY gained. Adjuvanted IIV3 cost‐effectiveness depends on its price and effectiveness (neither yet determined in the United States) but could be favored if its relative effectiveness is 15% greater than that of IIV3. Conclusion: From economic and public health standpoints, high‐dose IIV3 for adults aged 65 years and older is likely to be favored over the other vaccines, based on currently available data. The cost‐effectiveness of adjuvanted IIV3 should be reviewed after its effectiveness has been compared with that of other vaccines and its U.S. price is established.